Der Blaue Reiter. - Kunstmuseum Bern, Bern (Bern : Kunstmuseum Bern, 1986)
Arp, Hans ; Baldung, Hans ; Berg, Alban ; Bloch, Albert ; Burljuk, David ; Burljuk, Wladimir ; Campendonk, Heinrich ; Cézanne, Paul ; Delaunay, Robert ; Derain, André ; Le Fauconnier, Henri ; Gauguin, Paul ; Gimmi, Wilhelm ; Girieud, Pierre ; Van Gogh, Vincent ; Gontscharowa, Natalia ; El Greco ; Von Hartmann, Thomas ; Heckel, Erich ; Helbig, Walter ; Von Jawlensky, Alexej ; Von Kahler, Eugen ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Kubin, Alfred ; Kuniyoshi, Utagawa ; Larionov, Michail ; Lüthy, Oscar ; Macke, August ; Malewitsch, Kasimir ; Marc, Franz ; etc.
Der Blaue Reiter, Kunstmuseum Bern, 21. November 1986 bis 15. Februar 1987
boek